#### Answer

$p=\frac{qf}{q-f}$

#### Work Step by Step

Eliminate the fractions by multiplying the LCD $pqf$ to both sides of the equation:
$$\require{cancel}
(pqf) \cdot \left(\frac{1}{p} + \frac{1}{q}\right)=(pqf)(\frac{1}{f})
\\(pqf) \cdot \left(\frac{1}{p} + \frac{1}{q}\right)=pq$$
Distribute $pqf$:
$$pqf(\frac{1}{p}) + pqf(\frac{1}{q})=pq
\\\frac{pqf}{p} + \frac{pqf}{q}=pq
\\qf+pf=pq$$
Subtract $(pf)$ from both sides:
$$qf+pf-pf=pq-pf
\\qf=pq-pf$$
Factor out $p$:
$$qf=p(q-f)$$
Divide $q-f$ to both sides of the equation:
$$\frac{qf}{q-f}=\frac{p(q-f)}{q-f}
\\\frac{qf}{q-f}=p$$